The relationship between insulin resistance, bone mineral density, and fracture risk in postmenopausal women - Bazić-Sretenović Danijela; Veselinovć Mirjana; Nikolić-Turnić Tamara; Azanjac Anja; Korićanac Aleksandra; Tomić-Lučić Aleksandra (Vojnosanitetski Pregled)
Background/Aim. Skeletal muscles and bones are essential tissues that, in addition to supporting the body, are the primary site of postprandial glucose intake, which is significantly associated with insulin resistance. The aim of this study was to determine the effect of insulin resistance on bone mineral density (BMD) and fracture risk and re-evaluate the relationship between muscle properties and BMD and insulin resistance in postmenopausal women in Serbia. Methods. Homeostatic Model Assessment for Insulin Resistance (HOMA-IR) was calculated in postmenopausal women who were divided into two groups. The “cut-off” value of insulin resistance for the group with “Low HOMA-IR” was < 2, and for “High HOMA-IR” > 2. Fat mass (FM), lean mass (LM), and BMD were measured on the hip and spine using a densitometer with dual-energy X-ray absorptiometry. Results. FM and LM had an evident impact on BMD. The decrease in LM and fat buildup was associated with a higher incidence of insulin resistance. A positive correlation was confirmed between HOMA-IR and BMD on the spine and hip, but there was no correlation between insulin resistance and fracture risk. Conclusion. LM and FM have significant effects on BMD. The association between LM, FM, BMD and the onset of insulin resistance in postmenopausal women is confirmed. However, women with higher insulin resistance levels and higher BMD do not have a lower fracture risk.